Biological Deterioration of Wooden Components of Balla Lompoa Ri Galesong in South Sulawesi, Indonesia - Arif, Astuti; Putri, Giselawati; Soma, Andang Suryana; Syahidah; Syahribulan (Jurnal Sylva Lestari, 2024)
Balla Lompoa Ri Galesong, known well as the traditional house of the Takalar Regency, South Sulawesi, has become a historical building in Indonesia.  Nowadays, it still functions as a residence for the royal family, a repository for historical artifacts, and a venue for annual cultural performances. Maintaining and protecting buildings from damaging factors is crucial to maintaining their life and function. This research focuses on detecting the damage characteristics of wooden parts of buildings, identifying biological deterioration agents, and assessing the level of infestation. Data collection uses the visual detection method. The results showed that the activities of biodeterioration agents, namely subterranean termites (Microcerotermes serrula), drywood termites (Cryptotermes), powder-post beetles, wood-staining fungi, and wood-decaying fungi found on pillars, windows, doors, walls, floors, and ceiling. Most pillars are targets of attacks by wood-destroying organisms, characterized by the highest attack intensity (70.13%) and the moderate category in the degree of attack (50–74). Understanding and mitigating the damage to historic buildings is critical for implementing effective preventive measures. Keywords: Balla Lompoa Ri Galesong, biodeterioration agents, cultural heritage, wood biodeterioration